The Principle of Segendong Sepikul in the Inheritance Distribution System of the Muslim Community from the Perspective of Multidisciplinary Studies - Nur Alfy Syahriana; Zaenul Mahmudi (Fakultas Syariah, 2022)
This research was motivated by the researcher's interest in the principle of segendong sepikul which is applied in the Muslim community of Kandangtepus Village, Lumajang Regency, East Java, in distributing the inheritance. The purpose of this article is to describe the practice of the principle of segendong sepikul in the inheritance distribution model by the Muslim community of Kandangtepus Village. In the light of that, the researcher analyzes the said practice by using a multidisciplinary study in the present juridical-empirical research. Analyzed from the juridical-normative side, this practice is not in accordance with the provisions on the distribution of inheritance as found in the Sunni jurisprudences and the Compilation of Islamic Law. From a sociological perspective, this practice is appropriate with principles of justice according to Gustav and the concept of al-islah (reconciliation), as one of the teachings of Islam. Finally, the practice is likewise appropriate with the principles of Human Rights as it gives the person's rights according to the degree of the responsibility they carry.Keywords: Islamic inheritance; adat law; local wisdom.